Essential Oil from Melaleuca leucadendra: Antimicrobial, Antikinetoplastid, Antiproliferative and Cytotoxic Assessment - Lianet Monzote; Alexander M. Scherbakov; Ramón Scull; Prabodh Satyal; Paul Cos; Andrey E. Shchekotikhin; Lars Gille; William N. Setzer (Molecules, 2020)
Essential oils (EOs) are known for their use in cosmetics, food industries, and traditional medicine. This study presents the chemical composition and therapeutic properties against kinetoplastid and eukaryotic cells of the EO from Melaleucaleucadendra (L.) L. (Myrtaceae). Forty-five compounds were identified in the oil by GC-MS, containing a major component the 1,8-cineole (61%). The EO inhibits the growth of Leishmania amazonensis and Trypanosoma brucei at IC50 values <10 μg/mL. However, 1,8 cineole was not the main compound responsible for the activity. Against malignant (22Rv1, MCF-7, EFO-21, including resistant sublines MCF-7/Rap and MCF-7/4OHTAMO) and non-malignant (MCF-10A, J774A.1 and peritoneal macrophage) cells, IC50 values from 55 to 98 μg/mL and from 94 to 144 μg/mL were obtained, respectively. However, no activity was observed on Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Aspergillus niger, Candida parapsilosis, Microsporum canis, or Trypanosoma cruzi. The EO was able to control the lesion size and parasite burden in the model of cutaneous leishmaniasis in BALB/c mice caused by L. amazonensis compared to untreated animals (p < 0.05) and similar with those treated with Glucantime® (p > 0.05). This work constitutes the first evidence of antiproliferative potentialities of EO from M. leucadendra growing in Cuba and could promote further preclinical investigations to confirm the medical value of this plant, in particular for leishmaniasis treatment.